2013
DOI: 10.1353/hpu.2013.0165
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Correlates of Breast and Cervical Cancer Screening Among a Midwest Community Sample of Low-Acculturated Latinas

Abstract: Background Low adherence to cervical and breast cancer (CBC) screening recommendations contributes to high CBC mortality among Latinas. Purpose To estimate the prevalence of, and factors associated with, last 12-month Pap smear and mammogram receipt among a Midwest community sample of low-acculturated Latinas. Methods We conducted a cross-sectional study with 278 Latina immigrants in Dane County, Wisconsin. Participants completed a self-administered questionnaire. We estimated multivariate logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 38 publications
2
22
1
Order By: Relevance
“…Consistent with previous studies with Latino immigrants, 5961 our analyses showed a significant association between health insurance and health care utilization and between health insurance and availability of a regular source of care. Furthermore, additional analyses not shown in this paper suggest that availability of a regular source of care may mediate the association between health insurance and utilization of health care services among this sample.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies with Latino immigrants, 5961 our analyses showed a significant association between health insurance and health care utilization and between health insurance and availability of a regular source of care. Furthermore, additional analyses not shown in this paper suggest that availability of a regular source of care may mediate the association between health insurance and utilization of health care services among this sample.…”
Section: Discussionsupporting
confidence: 91%
“…Age, knowledge of screening recommendations, and having a regular health care provider were independently associated with both breast and cervical cancer screening in a sample of Latinas. 73 Similar results have been reported by researchers in this patient population. 78-81 Knowledge about screening recommendations is also low in Arab women and some studies indicate that even in women with adequate knowledge, screening is low.…”
Section: Introductionsupporting
confidence: 88%
“…39 However, many women do not adhere to these guidelines and many are not aware of these guidelines. 73,74 There is thus a clear need to identify factors that impact screening for racial/ ethnic minority women, particularly among immigrants and individuals with limited English proficiency to improve cancer screening rates.…”
Section: Introductionmentioning
confidence: 99%
“…Through a community-academic collaborative research project, we determined that Mixtec and Zapotec women from Mexico who are residing in Ventura County have extremely low mammography screening rates, even compared to other underscreened populations. For example, in a sample of low-acculturated Latinas residing in Wisconsin (Martinez-Donate, Vera-Cala et al 2013), lifetime receipt of mammogram among women 40 years and over was 74% (compared to 33% in our sample) and last 3-year receipt was 40% (compared to 22% who had a mammogram within the past 2 years in our sample). The proportion of indigenous women in our sample who reported breast feeding (94%), on the other hand, was extremely high compared to rates reported by African American women (47%), white women (72%) and Latinas (78%) (Centers for Disease and Prevention 2013).…”
Section: Discussioncontrasting
confidence: 53%